Advances in Subcutaneous Delivery Systems of Biomacromolecular Agents for Diabetes Treatment - Li C (Dove Medical Press, 2021)
Chen Li1 12 2,* Long Wan1 12 2,* Jie Luo1 12 2, Mingyan Jiang1 12 2, Keke Wang1 12 2 1Department of Pharmacy, The First Hospital of China Medical University, Shenyang, 110001, Liaoning, People’s Republic of China; 2School of Pharmacy, China Medical University, Shenyang, 110122, Liaoning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Keke WangDepartment of Pharmacy, The First Hospital of China Medical University, 155 Nanjing North Street, Shenyang, 110001, Liaoning, People’s Republic of ChinaTel +86-24-83282662Email wkkcc@163.comAbstract: Diabetes mellitus is a major threat to human health. Both its incidence and prevalence have been rising steadily over the past few decades. Biomacromolecular agents such as insulin and glucagon-like peptide 1 receptor agonists are commonly used hypoglycemic drugs that play important roles in the treatment of diabetes. However, their traditional frequent administration may cause numerous side effects, such as pain, infection or local tissue necrosis. To address these issues, many novel subcutaneous delivery systems have been developed in recent years. In this review, we survey recent developments in subcutaneous delivery systems of biomacromolecular hypoglycemic drugs, including sustained-release delivery systems and stimuli-responsive delivery systems, and summarize the advantages and limitations of these systems. Future opportunities and challenges are discussed as well.Keywords: diabetes mellitus, subcutaneous injection, insulin, glucagon-like peptide 1 receptor agonists, sustained-release, stimuli-responsive